Intra‐arterial cisplatin with concomitant radiation for advanced hypopharyngeal cancer12. (21st December 2012) - Nomura, Kenichiro; Takahara, Miki; Katayama, Akihiro; Kishibe, Kan; Kunibe, Isamu; Katada, Akihiro; Hayashi, Tatsuya; Harabuchi, Yasuaki
Abstract Objectives/Hypothesis: The current study evaluated the efficacy of radiation and concomitant high‐dose superselective intra‐arterial cisplatin infusion (RADPLAT) for patients with advanced hypopharyngeal cancer. Study Design: Retrospective, single‐institutional study. Methods: Between February 2004 and October 2010, 43 patients with T2N0 or worse cancer were given superselective intra‐arterial infusions of cisplatin (100‐mg/m2 or 75‐mg flat dose per week) with simultaneous intravenous infusions of thiosulfate to neutralize cisplatin toxicity and conventional external beam radiotherapy (60–66 Gy). Results: In total, three, seven, 21, and 12 patients were diagnosed with stage II, III, IVA, and IVB cancer, respectively. During the median follow‐up period of 34 months, the 3‐year overall survival, disease‐specific survival, and progression‐free survival rates for all patients were 52.2%, 68.2%, and 56.1%, respectively. The 3‐year local control and laryngoesophageal dysfunction‐free survival rates were 81.6% and 49.4%, respectively. No patient died because of treatment toxicity. Among grade IV toxicity, cerebral infarction (n = 1) and laryngeal necrosis (n = 1) resulting in laryngectomy were observed. Conclusions: Despite being a single‐institution experience, the results of the current study suggest that RADPLAT can achieve favorable survival rates and high rates of laryngeal preservation for patients with advanced hypopharyngeal cancers. Laryngoscope, 2012